Changes in bacterial communities and the volatilome of braised chicken with different packaging stored at 4 ℃. (May 2022) - Lei, Yang; Huang, Jichao; Cheng, Yiqun; Zhang, Yali; Huang, Tianran; Huang, Ming
Graphical abstract: Highlights: Bacterial diversities and volatilome of packaged braised chicken (BC) were assayed. Staphylococcus and Serratia were the abundant genera in MAP and VP samples. A total of 32 VOCs was detected in all the groups during storage. Staphylococcus positively correlated with the VOCs except heptanoic acid. The results provide insights to exploit appropriate control measures to BC spoilage. Abstract: The objective of this study was to investigate the effect of air packaging (AP), modified atmosphere packaging (MAP, 40% CO2 /60 % N2 ) and vacuum packaging (VP) on the dynamic changes of bacterial communities and volatile organic compounds (VOCs) in braised chicken stored at 4 ℃. Physicochemical characteristics and microbiological parameters were also measured. Results showed that MAP and VP groups obtained a slower growth rate of total viable count (TVC) and better sensory scores than AP groups. High throughput sequencing showed that Proteobacteria and Firmicutes were the dominant phyla in braised chicken samples. Additionally, different packaging conditions had significant effects on the succession of bacteria at the genus level. At the beginning of storage, Sphingomonas, Bradyrhizobium, Acinetobacter, Psychrobacter and Phyllobacterium dominated the microflora of braised chicken. However, on day 28, Staphylococcus and Serratia became the predominant genera in MAP and VP samples, respectively. Furthermore, thirty-two VOCs were detected in all braised chicken samples. Following the results of Spearman's correlation analysis, positive correlations were observed between Staphylococcus and all the compounds except for heptanoic acid. These results might provide valuable information regarding the quality improvement of braised chicken during refrigerated storage.